STUDY OF FRAMING DESIGN PRINCIPLES FROM THERMAL COMFORT ASPECTS IN TROPICAL HUMID CLIMATE CASE STUDY : HIGHRISE BUILDING, MIDRISE BUILDING AND LOWRISE BUILDING AREA TYPE IN SURABAYA - INTANA JANESONIA (NIM : 25616003), KETY
Infrastructure development in Surabaya changes urban form, such as replacing open spaces with high building density. Urban form transformation is one of many factors that can affect micro-climate condition in some areas. The phenomenon of urban form changing caused the increase of average air temperature in Surabaya City which constantly increased from 1980 to 2017. In 2017, the average air temperature reached 34.1 Ã‚Â° C which is included uncomfortable category or too hot compared to the standard of thermal comfort in Indonesia. This study aims to formulate the principles of designing urban areas based on thermal comfort. There are several methods is used, the first is quantitative descriptive analysis to classify the type of research area based on local climate zones, secondly analyze the climatic parameters that most influence on each type of area and the relationship of physical components to climatic parameters using Envi-Met simulation, regression analysis and quantitative descriptive analysis. And the last quantitative descriptive analysis to formulate design principles. As the results of the study it was found that in Tunjungan and Pemuda Street Areas (Highrise Building Area Types) the most influential climate parameters are wind speed. So the design principles for this type of area is prioritizes wind movement. The design principles that can bring greater wind into the area is by minimizing the ratio of built-up land (BCR), structuring building with smaller ratio at the end of the street corridor, structuring the road orientation and tree vegetation which in line with wind direction. In Penjaringan Sari Flat House Area (Type of Midrise Building Area) and Tegalsari Housing Area (Low rise Building Area Type) the most influential parameter is relative humidity. The design principles in the Penjaringan Sari Flat House Area (Type of Midrise Building Area) are the minimum provisions of FAR for increasing indicators of building height, structuring building distance, orientation of buildings, roads, and trees perpendicular to the direction of the sun. The design principles in the Tegalsari Housing Area (Lowrise Building Area Type) are the provision of maximum built-up land (BCR), structuring the distance between buildings, structuring the orientation of the building and the road in the direction of the wind and perpendicular to the solar radiation, the maximum provisions of FAR, the addition of trees on open space and minimize the availability of water bodies.